Constraints on particle acceleration in SS433/W50 from MAGIC and HESS observations - Ahnen, M. L.; Ansoldi, S.; Antonelli, L. A.; Arcaro, C.; Babie, A.; Banerjee, Biswajit; Bangale, P.; De Almeida, U. Barres; Barrio, J. A.; Gonzalez, J. Becerra; Bednarek, W.; Bernardini, Elisa; et al. (Astronomy & Astrophysics, 2018)
Context. The large jet kinetic power and non-thermal processes occurring in the microquasar SS 433 make this source a good candidate for a very high-energy (VHE) gamma-ray emitter. Gamma-ray fluxes above the sensitivity limits of current Cherenkov telescopes have been predicted for both the central X-ray binary system and the interaction regions of SS 433 jets with the surrounding W50 nebula. Non-thermal emission at lower energies has been previously reported, indicating that efficient particle acceleration is taking place in the system.
CRIS-Team WoS Importer:2020-01-15
Keywords: X-rays: binaries; Gamma rays: general; ISM: jets and outflows; Stars: black holes